Crosslinguistic Research in Syntax and Semantics: Crosslinguistic Research in Syntax and Semantics - Raffaella Zanuttini, Héctor Campos, Elena Herburger, and Paul H. Portner (Georgetown University Press, 2006)
This volume in the 2004 Georgetown University Round Table on Languages and Linguistics (GURT) series comes from the conference that took place March 26–29, 2004, with the theme Comparative and Crosslinguistic Research in Syntax, Semantics, and Computational Linguistics. While the conference was open to any research within this broad theme, the conference announcement noted that presentations focusing on the following issues were especially welcome: the syntax and semantics of clause types; syntactic variation across varieties of English; the internal structure of the noun phrase; negation, negative polarity, and negative concord; tense and aspect in formal and/or computational semantics; microvariation in the left periphery of the clause; and linguistic typology for machine translation. The main session in the conference had space for thirty-two presentations chosen from 126 submitted abstracts, in addition to seven presentations by the following invited speakers: Paola Benincà, Marcel den Dikken, Liliane Haegeman, James Mc- Closkey, Toshiyuki Ogihara, Colin Phillips, and Henriëtte de Swart. The presentations were evenly chosen from the abstracts submitted in the areas of syntax and semantics, with a small number in computational linguistics (reflecting the small number of abstract submissions in this area). In addition to the talks in the regular sessions, other conference events included two well-attended poster sessions, where twenty-four posters were displayed; a lively panel discussion on methodological issues in the study of English dialects, led by Judy Bernstein (William Paterson University), Ralph Fasold (Georgetown University), Simanique Moody (New York University), and Christina Tortora (College of Staten Island, CUNY); a tutorial on computational tools for linguists, organized and conducted by Inderjeet Mani (Georgetown University); and a postconference workshop on clause typing and the left periphery, which included the presentation of six papers and ample time for discussion.